Heat stress-induced heat shock protein 70 (HSP70) expressions among vulnerable populations in urban and rural areas Klang Valley, Malaysia - Muhamad, Siti Nurfahirah; Md Akim, Abdah; Lim, Fang Lee; Karuppiah, Karmegam; Mohd Shabri, Nur Shabrina Azreen; How, Vivien (Springer Nature, 2025)
BACKGROUND: As climate change raises global temperatures, there remains a notable gap in understanding the body’s mechanisms of heat stress defense exhibited by Heat Shock Protein (HSP) within the populations. OBJECTIVE: This study aims to investigate the expression level of HSP70 in response to indoor heat exposure among vulnerable populations in both urban and rural settings. METHODS: A comparative cross-sectional was conducted among 108 participants from urban and rural areas in Klang Valley, Malaysia. The study included face-to-face interviews, indoor heat exposure monitoring, and thermal stress classification using the Universal Thermal Climate Index (UTCI). HSP70 gene and protein expressions were analyzed using reverse-transcription quantitative polymerase chain reaction (RT-qPCR) and HSP70 High Sensitivity Enzyme-linked Immunosorbent Assay (ELISA), respectively. RESULTS: Urban areas experienced signficantly higher UTCI heat exposure levels than rural areas (p < 0.001). In response to heat stress, vulnerable populations in urban areas exhibited higher HSP70 gene relative expression and HSP70 protein expression. A significant mean difference in the plasma HSP70 protein expression was observed between the two groups (p < 0.001). The linear mixed model (LMM) revealed a significant association between UTCI heat exposure levels and HSP70 gene and protein expression in both groups (p < 0.001).